Photodegradation of Orange II under visible light using Cu–Ni/TiO2: Effect of calcination temperature - Riaz, Nadia (Elsevier, 2012)
The decolorization of Orange II was studied under visible light using bimetallic Cu–Ni/TiO2 prepared via precipitation method. Photocatalysts with different Cu:Ni mass compositions were prepared and the effect of calcination temperatures on the Orange II removal was investigated. The raw photocatalysts were activated by calcination at three different temperatures (180 ◦C, 200 ◦C and 300 ◦C) for 1 h duration. Photocatalysts were characterized using thermogravimetric analysis, Fourier-transformed infrared spectroscopy, powder X-ray diffraction and field-emission scanning electron microscopy, high resolution transmission electron microscopy, diffuse reflectance UV–Vis spectroscopy, temperature programed reduction studies and surface area analysis employing Brunauer–Emmet–Teller method. The photocatalytic degradation of Orange II was performed under the irradiation of visible light (500 W halogen lamp) at pH 6.8. The extent of Orange II degradation with initial concentration of 50 ppm was monitored using UV–Vis spectroscopy and at the end of the reaction, total organic carbon analysis (TOC) was conducted. Results from UV–Vis spectroscopy showed that high percentage of Orange II removal was achieved for Cu–Ni/TiO2 photocatalysts calcined at 180 ◦C and 200 ◦C compared to 300 ◦C. In addition, these photocatalysts also displayed lower TOC values as compared to the photocatalyst calcined at 300 ◦C. The best performing Cu–Ni/TiO2 photocatalyst has 9:1 Cu:Ni mass composition and calcined at 180 ◦C giving 100% Orange II removal with 16.1 ppm TOC value. Although the results from UV–Vis spectroscopy showed 100% Orange II removal, TOC analysis indicated the presence of organic compounds derived from the dye degradation process.